A Systematic Review of the Literature on Decision Making in Capital Budgeting - Usman, Asri; Mediaty, Mediaty; Mudasir, Allfina; Femmy, Irensa; Izzah, Sri Nurul (Amkop Management Accounting Review (AMAR), 2025)
This study aims to systematically review the literature on decision-making in capital budgeting, focusing on influencing factors, evaluation methods, and challenges encountered in practice. The research method employs Systematic Literature Review (SLR) analysis with the assistance of Watase Uake, Publish or Perish, ScienceDirect, Emerald, MDPI, SSRN, Scopus, Google Scholar, and Sinta, resulting in 27 relevant articles published between 2015 and 2025 that align with the research topic. The findings reveal that capital budgeting decisions are influenced by internal factors such as managerial competence, corporate governance, and information quality, as well as external factors including economic uncertainty, regulation, technology, and sustainability pressures. Traditional methods such as NPV, IRR, and Payback Period remain dominant, while advanced approaches like Real Options, Fuzzy Logic, and sustainability-based frameworks are emerging. Key challenges include data limitations, market volatility, methodological complexity, and behavioral bias. The study provides practical insights for financial managers to improve investment evaluation by integrating influencing factors, methods, and challenges into a more adaptive decision-making framework.